Intuicja i precyzja w kształceniu matematycznym ekonomisty - Klepacz, Halina; Porazińska, Elżbieta; Żółtowska, Elżbieta (Intuition and Precision in Mathematical Education of an Economist, 2006)
In this article the authors want to attract attention to two aspects of mathematical educational process in economic studies; precision and intuition. Most often a student who begins learning in a high school is neither good at mathematical knowledge nor at correct association ways of different notions and exact conclusions. University teachers of science must not only acquaint students with new knowledge but eliminate wrong habits as well. They have to develop the ability of precise expressing and describing problems. Apart from necessary mathematical precision it is extremely important to improve students mathematical intuition, which is difficult to achieve.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1117, s. 77-83